Analisis Rasch Model Bystander Effect Pada Bullying di SMP Negeri Mojokerto: Rasch Model Analysis of Bystander Effect on Bullying in Junior High School in Mojokerto - Arfida Reta Sandeva; Widyastuti Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Bullying remains a critical issue in Indonesian junior high schools, where bystanders play a central role in either reinforcing or preventing aggressive behavior. Understanding students’ bystander tendencies is essential for developing effective school-based interventions. Objective: This study aimed to analyze the bystander effect in bullying cases among junior high school students using the Rasch measurement model. Methods: A descriptive quantitative design was employed involving 278 students from SMP Negeri 2 Pungging, Mojokerto, selected through proportionate stratified random sampling. Data were collected using the School Bullying Bystander Scale (SBBS), adapted into Indonesian. Responses were analyzed using the Rasch Model to examine person measures, item functioning, and Wright maps. Differences across grade levels were tested using the Kruskal–Wallis method. Results: The findings indicate that most students tend to assume the defender role in bullying situations. However, significant differences were identified across grade levels, particularly in probully tendencies, with Grade VIII students showing higher scores compared to Grades VII and IX (p < 0.05). Rasch analysis revealed that 62 respondents were misfitting, suggesting response inconsistencies. One student demonstrated extreme probully behavior, while five students showed uncertainty in responding. Overall instrument reliability was acceptable, supporting the use of SBBS for assessing bystander roles. Conclusion: Although defender behavior predominates, the presence of probully tendencies—especially among Grade VIII students—highlights the need for targeted school interventions. The Rasch Model effectively mapped student bystander profiles and identified atypical response patterns. Future studies should involve broader samples and integrate intervention-based approaches to strengthen anti-bullying programs. Keywords: Bystander Effect, School Bullying, Junior High School, Rasch Model, Student Behavior Key Findings Highlights: • Most students exhibited defender tendencies in bullying situations.• Grade VIII students showed significantly higher probully behavior than other grades.• Rasch analysis detected 62 misfitting respondents, indicating response inconsistency and measurement noise.